2020
DOI: 10.15547/bjvm.2168
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of equine herpes virus-1 in endemic area of Egypt with risk factors assessment

Abstract: Although equine herpesvirus-1 (EHV-1) infection occurs throughout the world; causing various health problems within horse population such as respiratory disease, abortion and myeloencephalopathy, there is information shortage concerning the epidemiological situation of EHVs in Egypt. This paper is the first study of EHV-1 prevalence rate in Monufia province (as a model for other pro­vinces). During 2015, two hundred and seventy serum samples from EHV non-vaccinated horses were randomly collected from 9 centres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
1
3
2
Order By: Relevance
“…Analysis of the results obtained from EHVs cases outlines that EHV-1 is the most prevalent type detected, with an overall percentage of 62%. This correlates with other studies done in Egypt (64%) 24 and the Republic of Serbia (59.1%), 25 but relatively higher than the findings in Ethiopia (7.5%) 18 and Algeria (2%). 26 In the current study, identification of EHV-2 in 53% equids with signs of respiratory disease is relatively higher than other studies reported around the world.…”
Section: Discussionsupporting
confidence: 90%
“…Analysis of the results obtained from EHVs cases outlines that EHV-1 is the most prevalent type detected, with an overall percentage of 62%. This correlates with other studies done in Egypt (64%) 24 and the Republic of Serbia (59.1%), 25 but relatively higher than the findings in Ethiopia (7.5%) 18 and Algeria (2%). 26 In the current study, identification of EHV-2 in 53% equids with signs of respiratory disease is relatively higher than other studies reported around the world.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, in urban areas people kept mostly male horses as status symbol and hobby purpose. Similarly, on contrary to present study, some studies found age as an important factor that can influence the occurrence of disease (Ata et al 2020;Hafshejani et al 2015). Standardbred and thoroughbred horses have higher susceptibility than local Arabian and Turkoman breeds (Hafshejani et al 2015).…”
Section: Haematological Analysis Of Sero-positive and Seronegative Horsescontrasting
confidence: 99%
“…Epidemiological Aspects of Equine Herpes Virus Infection in South Gujarat, India as an influential factor on occurrence of disease (Hafshejani et al 2015). On contrary to findings of present study, in certain studies higher sero-prevalence of EHV-1 was found in females than in males (Ata et al 2020;Senthil and Parameswaran, 2014). This might be due to unequal gender wise sample collection.…”
Section: Haematological Analysis Of Sero-positive and Seronegative Horsescontrasting
confidence: 86%
See 1 more Smart Citation
“…Many studies were performed about EHV-1, 2, 4, and 5 in both healthy and unhealthy horses that different and contrary results were found. Ata et al (2020) were found the seroprevalence of EHV-1 64% in Monu a, Egypt. However, Amer et al (2011) investigate the seroprevalence of EHV-1,2,4 via polyclonal antibody pool technical ELISA and they found the seroprevalence was 36% in Arabian horses in Egypt.…”
Section: Discussionmentioning
confidence: 84%